Angiotensin-Converting Enzyme Genetic Polymorphism rs4343 as Risk of Diabetic Nephropathy in Jambi-Malay Population - Elfiani, Elfiani; Puspasari, Anggelia; Arif, Cut Wulan; Maharani, Citra; Ali, Zulkhair; Suhaimi, Novadian; Effendi, Ian; Suprapti, Suprapti; Shafira, Nyimas Natasha Ayu (Molecular and Cellular Biomedical Sciences, 2024)
Background: Diabetic nephropathy (DN) is one of the frequent complications of type II diabetes mellitus (T2DM) in Jambi province. Controlling blood glucose and blood pressure does not guarantee DN prevention, since genetic factors may also contribute to this disease. Multi-ethnic studies showed that one of the strongest genetic factors associated with DN was single nucleotide polymorphism rs4343 of angiotensin-converting enzyme (ACE) gene. Study regarding phenotype-genotype association of ACE rs4343 and DN has not yet been performed in Jambi Province, which is dominated by Malay ethnicity. This study was conducted to reveal the association between ACE rs4343 and the risk of DN in the Jambi-Malay population.Materials and methods: This was a cross-sectional study involving 75 subjects (44 with DN and 31 without DN) who suffered from T2DM and hypertension. DN was defined as albumin to creatinine ratio (ACR) ≥30 mg/g. Genotyping was performed with one-step tetra amplification refractory mutation system-polymerase chain reaction (PCR) using specific primer for ACE rs4343. Bivariate and multivariate analyses were performed to analyze the genetic risk for DN.Results: The bivariate analysis showed the proportion of DN subjects was higher than non-DN within the AG genotype (11:1) than within the AA (33:30) genotype. This difference was statistically significant (p=0.012; OR (95% CI): 10.00 (1.22-82.15)). Multivariate analysis showed that AG genotype (p=0.047; OR (95% CI): 10.04 (1.03-97.31)) and uncontrolled blood pressure (p=0.001; OR (95% CI): 6.72 (2.08-21.71)) were the risk factors of DN in the Jambi-Malay population.Conclusion: Polymorphism of ACE rs4343 is a risk factor of DN in the Jambi-Malay Population.Keywords: rs4343, angiotensin-converting enzyme gene, diabetic nephropathy, Malay, Jambi